A) 5x²y+1/y² dla x=√2 , y=-0,5

b) -2[x/3- y/4+ z/5 ×(-x+y-z)]² dla x= -6 , y= 8 ,z= 10

c) √9x⁴-2y³+5z² dla x=-1/3 , y = -0,5 , z= -√5/5

d) (-3ab²c²de⁴)³ dla a= -√2 , b= 3/4 , c = -(2/3), d=√8,e=-1

e) -3(-6x²+4) 6(2-3x³)
---------------- - ------------- dla x= -1⅓ ,
4(5-3x) 10-9x²

f) 6x² - 4x⁴ + 2x⁶ - 0,25x⁸ dla x= √2

1

Odpowiedzi

2009-11-12T21:18:40+01:00
A) 5*2*(-0,5)+1/-0,5=-7
b)-2[-6/3-8/4+10/5*(-6)*(-6*8*10) = -2[-2-2-12*(-480) = -2*5756=-11512
c)3*(-1/3)⁴-2*(-0,5)³+5*1²=1/243-0,25+5
d)(-3*(-√2)*9/16*4/9*√8*1)³=(3√2*9/16*4/9*√8)³=(3√2*1/4*√8)³=(7*1/4)³=5 i 23/64
e)18x-12przez20-12x-12-18x³przez10-9x²=3x-3przez5-2x-6-18x³przez5-9x²=3*(-1i1/3)³przez5-9*(-1i1/3)²=1przez2i2/3-6-42i2/3przez5-16=1przez2i2/3-37i1/3przez-11=1przez2i2/3-3i13/33=2i2/3+3i13/33=88/33+112/33=200/33=6i2/33
f)6*2-4*4+2*8-0,25*16=12-16+16-4=8